Lifestyle Risk Factors And Their Association With Diabetes And Hypertension In A Community Population: Cross Sectional Study - Kumar Verma, Tapan; Ahmad, Siraj; Belal Hassan, Syed; Kalra, Aastha; Pathak, Abhishek (Journal of Neonatal Surgery, 2025)
Non-communicable diseases (NCDs), particularly type 2 diabetes mellitus (T2DM) and hypertension, are emerging as critical public health issues in semi-urban and rural communities. These conditions are largely driven by modifiable lifestyle risk factors such as physical inactivity, unhealthy dietary patterns, tobacco and alcohol use, and inadequate sleep. Early identification of these risk factors and their association with disease prevalence is vital to developing effective community-based prevention strategies. A cross-sectional study was carried out among 410 adults aged 30 years and above residing in the Rural Health Training Center (RHTC), Sansarpur, Lucknow. Data collection involved structured interviews capturing sociodemographic details, lifestyle habits, and known medical history. Anthropometric measurements were recorded, and blood pressure was measured using standardized protocols. Fasting blood glucose was assessed using a glucometer. The diagnosis of hypertension and diabetes was based on established clinical criteria. Statistical analysis included descriptive statistics and chi-square tests to evaluate associations between lifestyle factors and disease status. The prevalence of hypertension and diabetes was found to be 34.1% and 23.7%, respectively. Significant associations (p < 0.05) were observed between these conditions and high BMI, physical inactivity, unhealthy diet, tobacco use, and alcohol consumption. These findings highlight the urgent need for lifestyle interventions targeting behavior modification. Strengthening community-level awareness and preventive health services could substantially reduce the growing burden of NCDs in similar populations.